Resource allocation for multi-cell full-duplex wireless powered communication networks - Muhammad Shahid Iqbal; Yalcin Sadi; Syed Adil Abbas Kazmi; Sinem Coleri (EURASIP Journal on Wireless Communications and Networking)
Abstract Wireless powered communication networks (WPCNs) are crucial in achieving perpetual lifetime for the machine-type communication (MTC) and Internet of things (IoT) in fifth-generation (5G) communication and beyond networks. Practical WPCNs cover a broad region and have a significant number of sensors, requiring multi-cell deployment. We investigate the minimum length scheduling problem for a multi-cell full-duplex WPCNs to find the optimal power and schedule by considering the simultaneous transmission, maximum transmit power and energy causality constraints for the users. The optimization problem to minimize the schedule length is combinatorial, thus, difficult to find the global optimum solution. To overcome this, we divide the problem into two subproblems, i.e., power control problem (PCP) and the scheduling problem. Then, we present the optimal polynomial time algorithm for the PCP based on the use of the bisection method and evaluation of the Perron–Frobenius criteria. Then, by using the PCP solution, we calculate the optimal transmission time for the users that are scheduled by the scheduling algorithm. For the scheduling problem, we define a penalty function that represents the gain of simultaneous transmission over the individual transmission of the users and we show that the minimization of schedule length is similar to the minimization of sum of penalties. Following the optimum analysis of the proposed penalty metric, we present a heuristic algorithm that tries to minimize the sum penalties of the simultaneously transmitting users over the schedule. Through extensive simulations, we show significant gains of scheduling for concurrent transmissions over individual transmissions.